Sistema de ejercicio para mejorar el gesto técnico en la recepción y control del balón en futbolistas en edades de 10 -12 años del Club Deportivo Atlético Jujan - Alvarado Carpio, Frank Alejandro (2024)
This presents results from a cross-sectional study carried out at Club Deportivo Atlético Jujan, about the technical gesture in receiving and controlling the ball in soccer players aged 10 -12 years. The importance of this scientific work is essentially expressed in two results, in the diagnosis obtained, through which the scientific methodological shortcomings of the coaches investigated and the technical level of the footballers in the gestures investigated, as well as in the elaboration of the methodological bases for the realization of a system of actions aimed at solving the assumed scientific problem, which served as a basis for the development of the research activity that served as the basis for the writing of this final thesis report, the above-mentioned representing the main findings. reached. To collect and analyze the required information, empirical and theoretical methods from scientific research were used. The results according to the scope that supports them can benefit coaches and athletes.